Clinical Validity and Utility of Tumor-Infiltrating Lymphocytes in Routine Clinical Practice for Breast Cancer Patients: Current and Future Directions - Wein, Lironne; Savas, Peter; Luen, Stephen J.; Virassamy, Balaji; Salgado, Roberto; Loi, Sherene (Frontiers in Oncology, 2017)
The interest in tumor-infiltrating lymphocytes (TILs) as a prognostic biomarker in breast cancer has grown in recent years. Biomarkers must undergo comprehensive evaluation in terms of analytical validity, clinical validity and clinical utility before they can be accepted as part of clinical practice. The International Immuno-Oncology Biomarker Working Group has developed a practice guideline on scoring TILs in breast cancer in order to standardize TIL assessment. The prognostic value of TILs as a biomarker in early-stage breast cancer has been established by assessing tumor samples in thousands of patients from large prospective clinical trials of adjuvant therapy. There is a strong linear relationship between increase in TILs and improved disease-free survival for triple-negative and HER2-positive disease. Higher levels of TILs have also been associated with increased rates of pathological complete response to neoadjuvant therapy. TILs have potential clinical utility in breast cancer in a number of areas. These include prediction of responders to immune checkpoint blockade, identification of primary HER2-positive and triple-negative patients who have excellent prognoses and may thus be appropriate for treatment de-escalation, and potentially incorporation into a neoadjuvant endpoint which may be a better surrogate maker for drug development.